Effects of physical activity on academic burnout among rural left-behind children in China: the chain-mediated roles of loneliness and general self-efficacy - Chen, Jiaxi; Liu, Xiao; Xie, Jiaqi; Yang, Qian; Fan, Ziping; Peng, Dianhui; Wang, Yujuan; Lu, Chunxia (Frontiers in Psychology, 2025)
PurposeTo explore the impact of physical activity on academic burnout among rural left-behind children.MethodsIn total, 195 rural left-behind children of Furen Primary School in Yongzhou City by combining stratified and cluster sampling methods. Participants completed the Physical Activity Scale, the Academic Burnout Scale, the Loneliness Scale, and the General Self-efficacy Scale.Results(1) Empirical evidence indicates alarming rates of academic burnout among rural left-behind children in China. (2) Physical activity was significantly associated with reduced academic burnout. Our serial mediation model showed that physical activity had a significant direct effect on academic burnout (β = −0.231, 95% CI = [−0.308, −0.154]) in addition to significant chain-mediated effects on academic burnout via loneliness and general self-efficacy (β = −0.051, 95% CI = [−0.093, −0.018]); the more exercise participation, the lower the academic burnout among rural left-behind children. (3) These findings suggest that physical activity is an important interventional target when aiming to reduce academic burnout.ConclusionPhysical activity can affect rural left-behind children’ academic burnout both directly and through mediating effects. Loneliness and general self-efficacy partially mediate the impact of physical activity and academic burnout.